Application of the Hungarian Assignment Method to Minimize Normal Cases in Cinderella Tempe Chips MSMEs - Pesta Gultom; Ester Sabrina Aruan; Ribka Callista Simangunsong; Viona Anggraini br Ketaren; Winda Rosianna Tampubolon (Outline Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economy, including the Cinderella Tempeh Chips MSME. To address efficiency and productivity challenges, an appropriate management approach is needed, one of which is the Hungarian minimization method for production assignment. This research explores the application of the Hungarian method to solve minimization assignment problems at the